Worldview, religion, and urban growth: a geopolitical perspective on geography of power and conception of space during Islamization in Java, Indonesia - Hafid Setiadi (IAIN Salatiga, 2021)
Discussion of Islamization is not only associated with the spread of religious values but also related to the activity of trade and the opening of the new lands. In Java, all three of these themes have occurred simultaneously and then experienced rapid development since the 15th century. During the 15th and 17th centuries, many Islamic kingdoms rose and fell by turns with variuos ideology and their economic and political motives. As a result, Java experienced a complex of territorialization. By a spatial-historical approach, this article shows how territorialization affects the fashion of the emergence and collapse of the cities in Java. The spatial dynamics of urban growth reflected changes in political space production run by each ruling actor. The city played a significant role as a symbol and an identity of the political power of the dominant regime.